Pengembangan Pembelajaran Matematika Diskrit Menggunakan Google Classroom pada Mahasiswa Pendidikan Matematika - Suarti Djafar; Hafsyah Hafsyah; Rustiani Rustiani (Journal on Education, 2023)
Google Classroom is a platform in the form of an LMS (learning management system) which is provided free or unpaid by Google. Google classroom is integrated with email, so it's easy to use (user friendly). Google classroom makes it easy for teachers and lecturers to do distance learning, so that learning becomes efficient, effective and interactive. This study uses a quantitative descriptive research method (Maolani & Cahyana, 2016). The quantitative approach used is in the form of questionnaires and interviews. The purpose of this study is to describe student learning using the Google Classroom Application in Discrete Mathematics courses during the Covid-19 pandemic. This research carried out from the odd semester of the 2021/2022 academic year to 10 students in the fifth semester of the Discrete Mathematics course, the Mathematics Education Study Program. useful for helping plan events, send surveys, give students or others quizzes, or gather simple information in an efficient way. Interviews were conducted at the end of online teaching and learning activities. Data analysis was performed using excel to calculate the percentage and average value. Based on the indicators of the application of the Google Classroom Application, it shows that the average student answer is 75.5% agree and 25.5% disagree. These results show that the application of Google Classroom gets good responses from students, so that it can be used for learning in Discrete Mathematics courses.